Exploring the Dynamics of E-Learning: From the Early Era to AI Integration and a Comparative Analysis of Implementation Across Educational Levels - Rizki Anggi Zulfikri (Manajia: Journal of Education and Management, 2025)
Digital transformation has made e-learning an essential paradigm in higher education, offering superior flexibility (anytime, anywhere). This article aims to analyze the historical development of e-learning, compare its implementation models in schools and universities, and critically evaluate its advantages and disadvantages. This research employs a literature review with a qualitative descriptive approach and critical analysis. Data sources include reputable primary and secondary literature, collected through a structured documentation study and analyzed using narrative synthesis and content analysis to interpret pedagogical and technological concepts. E-learning has evolved from passive document transfer (1990s) to adaptive systems powered by AI and VR (2020s). Its implementation in higher education is driven by andragogy, demanding high student autonomy in analysis and exploration, in contrast to the structured school model. Key advantages include flexibility in time and the development of digital skills through learning analytics. However, critical challenges include the digital divide, the risk of social isolation, and the difficulty of managing students' intrinsic motivation due to the lack of physical supervision. Optimal implementation of e-learning in higher education must adopt a hybrid-adaptive model that integrates online sessions (for adaptive knowledge transfer) with offline/face-to-face sessions (for critical discussion and collaborative practice). Continued investment in lecturers' digital pedagogy and interactive content design is required to ensure equity of access and quality of learning.